PENGARUH PENERAPAN E-SPT, KESADARAN WAJIB PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA KARAWANG UTARA - Alfarisi, Gusti Denny; Mahpudin, Endang (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.10.TAHUN 2020DO - 10.24843/EEB.2020.v09.i10.p03, 2020)
This study aims to determine the effect of E-SPT Application, Taxpayer Awareness, and Tax Sanctions on Taxpayer Compliance at KPP Pratama Karawang Utara. The sampling technique in this study was carried out using purposive sampling. The data collection method used in this study was to distribute questionnaires to individual taxpayers who were used as research samples. Testing and data analysis were tested using multiple regression analysis. The results showed that (1) The implementation of E-SPT partially has a positive and significant effect on Taxpayer Compliance, (2) Taxpayer Awareness partially has a positive and significant effect on Taxpayer Compliance, (3) Partially Tax Sanctions have a positive and significant effect. to Taxpayer Compliance. In addition, simultaneously the research results show that (4) Implementation of E-SPT, Taxpayer Awareness, and Tax Sanctions simultaneously have a positive and significant effect on Taxpayer Compliance.